After the Break-Up: The Relational and Reputational Consequences of Withdrawals from Venture Capital Syndicates - Zhelyazkov, Pavel I.; Gulati, Ranjay (Academy of Management Journal, 2016)
Organizational theorists are increasingly interested in the antecedents of terminating interorganizational relationships, but have paid little attention to the disruptive consequences of such terminations on future tie formations. To redress this imbalance, the present study focuses on how venture capital (VC) firms’ withdrawals from VC syndicates are associated with their subsequent syndication in the period from 1985 to 2008. We argue that withdrawals disrupt the relationships of the withdrawing VC firms with the coinvestors and reduce the likelihood of them entering into subsequent exchange (relational consequences). Furthermore, public information on the withdrawals can undermine the withdrawing VC firm’s reputation for reliability, making it a less desirable exchange partner overall (global reputational consequences). Finally, we find that abandoned coinvestors can spread negative private information about the withdrawing firm, reducing its chances of syndication with their other network contacts (local reputational consequences). We also show that the global and local reputational consequences attenuate each other, due to redundancy in the content of the information each provides. We discuss the implications of our theory for the research on network dynamics and reputation.